Preparation method of hollow super-structure Co-coated CN composite material, manufacturing method of hydrogen peroxide sensor and hydrogen peroxide detection method

The preparation of hollow superstructure Co@C/N composite materials through co-precipitation method and high-temperature pyrolysis has solved the stability and conductivity problems of MOF materials in the field of electrochemical detection, and achieved high sensitivity and low detection limit hydrogen peroxide electricity Chemical sensor.

CN119470584APending Publication Date: 2025-02-18HUBEI ENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411443528.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, MOF materials have problems such as poor stability and poor conductivity in the field of electrochemical detection, which leads to less application in the field of chemically modified electrodes.

Method used

ZIF material with bimetallic centers was prepared by co-precipitation method, and a hollow superstructure Co@C/N composite material was obtained by selective etching and high-temperature pyrolysis, which was used to construct a hydrogen peroxide electrochemical sensor.

Benefits of technology

It improves the stability and conductivity of the material, enhances the electron transmission rate, improves the sensitivity of the hydrogen peroxide electrochemical sensor, reduces the detection limit, and broadens the detection linear range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119470584A_ABST
    Figure CN119470584A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a Co-coated C / N composite material with a hollow super structure. Preparing a bimetal-centered ZIF material by using a coprecipitation method; a hollow super-structure ZIF material is obtained through selective etching; and performing high-temperature pyrolysis to obtain the hollow super-structure Co-coated C / N composite material. The invention also relates to a method for constructing a hydrogen peroxide electrochemical sensor by using the hollow super-structure Co-coated C / N composite material, the hollow super-structure Co-coated C / N material and Nafion are ultrasonically mixed and then dispensed on a working electrode, and the modified working electrode is obtained and used for constructing the hydrogen peroxide electrochemical sensor. The invention also relates to a method for detecting hydrogen peroxide using the hydrogen peroxide electrochemical sensor. The hollow super-structure Co (at) C / N composite material which is high in stability, good in conductivity, rich in active sites and controllable in morphology structure is conveniently prepared at low cost; the electron transmission rate of the material is improved; the sensitivity of the hydrogen peroxide electrochemical sensor is improved, the detection limit is reduced, and the detection linear range is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation and application of functional composite materials, and in particular to a method for preparing a hollow superstructure Co@CN composite material, a method for manufacturing a hydrogen peroxide sensor, and a method for detecting hydrogen peroxide. Background Art

[0002] Electroanalytical chemistry is a type of analytical method based on measuring the electrical response of a chemical system or sample. It regards the object to be measured as a component of a chemical cell, measures certain physical quantities of the chemical cell through electrochemical sensors, and calculates the content of the measured substance or measures certain electrochemical properties of the substance. Electrochemical analysis has the advantages of low cost, simple operation, rapid detection and high sensitivity. Therefore, electrochemical analysis is widely used as a rapid and sensitive detection technology in biomolecule detection, food safety detection, pollution detection and other aspects. Chemically modified electrodes are an important part of electroanalytical chemistry. Chemically modified electrodes refer to the physical or chemical modification of the surface of an electrode made of a conductor or semiconductor to introduce molecules, ions or polymers with the desired chemical structure and properties on the electrode surface to achieve a specific purpose. How to modify the electrode, whether the modification method is reasonable, whether the modified electrode surface is uniform and other factors will greatly affect the electrochemical activity of the chemically modified electrode. Therefore, chemically modified electrodes are the foundation of chemically modified electrode research and application.

[0003] MOFs are a type of periodic three-dimensional porous crystalline materials with nanopores formed by metal ions and organic ligands connected by coordination. MOFs materials have attracted much attention in the field of electrochemistry due to their high specific surface area and unique porous morphology. By adjusting the morphology and size of MOFs, it will be beneficial to obtain higher performance. The hollow super-structured MOFs materials prepared using simple MOFs as precursors not only inherit the original porosity and large specific surface area of ​​MOFs, but also have the advantages of rich reactive active sites, controllable morphology, structure and composition, and good physical and chemical stability, showing excellent electrochemical activity. However, simple MOFs materials have disadvantages such as poor stability and poor conductivity in electrochemical detection, which makes simple MOFs relatively rare in the field of chemically modified electrodes. Using MOFs materials as precursors to form MOFs-derived materials such as porous metal oxides or metal@C / N porous materials during heat treatment, in addition to the advantages of MOFs, this material also has the characteristics of high stability and good conductivity. Therefore, the application of MOFs-derived materials in electrochemical catalysis and electrochemical analysis has greatly promoted electrochemical research.

[0004] Existing technologies for detecting hydrogen peroxide include titration analysis, spectrophotometry, fluorescence spectrophotometry, high performance liquid chromatography and near infrared spectroscopy. These methods have the disadvantages of low sensitivity, high detection cost and troublesome sample pretreatment. Compared with these methods, the electrochemical sensor method has high sensitivity, good linear range, wide detection limit, short detection time and low cost. However, due to the special morphology, structure and composition of simple MOF materials, there are many unavoidable problems in the field of electrochemical detection, such as metal ions being wrapped by organic matter, resulting in low conductivity of metals, and low stability of MOF materials in electrochemical systems. After improving this sensor to address these shortcomings, these shortcomings have been overcome, so hydrogen peroxide sensors are expected to be widely used in various fields. Summary of the invention

[0005] In view of the above problems, the present invention provides a method for preparing a hollow super-structure Co@CN composite material, a method for manufacturing a hydrogen peroxide sensor and a method for detecting hydrogen peroxide, the purpose of which is to conveniently and inexpensively prepare a hollow super-structure Co@C / N composite material with high stability, good conductivity, abundant active sites and controllable morphology; to improve the electron transfer rate of the material; to improve the sensitivity of the hydrogen peroxide electrochemical sensor, to reduce the detection limit, and to broaden the detection linear range.

[0006] To solve the above problems, the technical solution provided by the present invention is:

[0007] The preparation method of the hollow superstructure Co@C / N composite material comprises the following steps:

[0008] Sa100. Preparation of ZIF materials with bimetallic centers by coprecipitation; washing and dispersing the first dispersion prepared after the reaction;

[0009] Sa200. The first dispersion prepared in step Sa100 is selectively etched to obtain a hollow super-structure ZIF material;

[0010] Sa300. The hollow super structure ZIF material prepared in step Sa200 is subjected to high temperature pyrolysis to obtain a hollow super structure Co@C / N composite material.

[0011] Preferably, the step Sa100 comprises the following specific steps:

[0012] Sa110. Weigh and dissolve the manually preset mass of zinc and cobalt divalent metal salts;

[0013] Sa120. Weigh the manually preset mass of the organic ligand 2-methylimidazole and dissolve it in the solvent obtained in step Sa110, and then dissolve it by ultrasound;

[0014] Sa130. The mixed solution obtained in step Sa120 is mixed and allowed to stand to produce the ZIF material of the bimetallic center; the standing time ranges from 2h to 12h;

[0015] Sa140. After the reaction in step Sa130 is completed, the first dispersion is obtained by washing and dispersing.

[0016] Preferably, the step Sa200 comprises the following specific steps:

[0017] Sa210. The first dispersion obtained in step Sa140 is added to an organic acid solution for etching; the etching time ranges from 2h to 12h;

[0018] Sa220. The solution obtained in step S210 is centrifuged, washed and dried to obtain a hollow super-structure ZIF material.

[0019] Preferably, the step Sa300 comprises the following specific steps:

[0020] Sa310. The hollow super structure ZIF material obtained in step Sa220 is placed in a tubular furnace, and then calcined in an inert gas atmosphere and maintained for a manually preset calcination time; the calcination temperature range is 600°C to 1200°C, and the heating rate is 2°C / min to 10°C / min;

[0021] Sa320. The product of step Sa310 is naturally cooled to room temperature and then taken out and ground to obtain the hollow superstructure Co@C / N composite material.

[0022] Preferably, the divalent metal salts of zinc and cobalt in step Sa110 include cobalt acetate and zinc acetate, and the amount ratio of zinc acetate to cobalt acetate is 20:1 to 100:1;

[0023] The organic acid solution in step Sa210 is benzoic acid, salicylic acid, citric acid or tannic acid; the concentration range of the organic acid solution is 0.01 mmol·L -1 ~0.1mmol·L -1 .

[0024] A method for constructing a hydrogen peroxide electrochemical sensor using the hollow superstructure Co@C / N composite material comprises the following steps:

[0025] Sb100. The bare glassy carbon electrode was polished, and after passing the inspection, it was ultrasonically cleaned with ethanol and distilled water respectively, and then dried;

[0026] Sb200. After the hollow super structure Co @ C / N composite material is ground, it is taken out according to the preset mass and then ultrasonically dispersed in a polymerizing agent solution to obtain a second dispersion;

[0027] Sb300. Take the second dispersion droplets and apply them to the bare glassy carbon electrode obtained after the treatment in step Sb100 and dry them naturally to obtain a bare glassy carbon electrode modified with a hollow superstructure Co@C / N composite material;

[0028] Sb400. The hydrogen peroxide electrochemical sensor is constructed by using a saturated calomel electrode as a reference electrode, a platinum wire electrode as a counter electrode, and a bare glassy carbon electrode modified with the hollow superstructure Co@C / N composite material as a working electrode.

[0029] Preferably, the manually preset mass in step Sb200 is within a range of 1 mg to 5 mg; the polymerizing agent is nafion and chitosan or isopropanol or DMF or ethanol; and the polymerizing agent-ethanol concentration is 1% to 5%.

[0030] The method for detecting hydrogen peroxide using the hydrogen peroxide electrochemical sensor comprises the following steps:

[0031] Sc100. The electrolyte is prepared using KOH solution;

[0032] Sc200. Cyclic voltammetry curve of the sample was measured by cyclic voltammetry at room temperature using an electrochemical workstation; Sc300. Chronoamperometric curve of the sample was measured by chronoamperometric response method at room temperature.

[0033] Preferably, the concentration range of the KOH solution prepared in Sc100 is 0.01 mol / L to 0.5 mol / L, which is used to prepare the hydrogen peroxide base solution;

[0034] The concentration range of the hydrogen peroxide base solution is 0.1 mmol / L to 20 mmol / L, and the base solution is used as a hydrogen peroxide standard solution for electrochemical determination.

[0035] Preferably, in the cyclic voltammetry method described in Sc200, the scan rate is 20 mV / s to 200 mV / s, the potential range is -2 V to +1 V, and the number of cycles is 0 to 20;

[0036] The concentration of hydrogen peroxide added in the chronoamperometric response method described in Sc300 is 0 mmol / to 1 mmol / L, and the time interval is 10 s / time to 100 s / time.

[0037] Compared with the prior art, the present invention has the following advantages:

[0038] 1. Since the present invention provides a preparation process of a hollow super-structure Co@C / N composite material, the process method is simple and the raw material price is low. The prepared hollow super-structure Co@C / N composite material has the characteristics of high stability, good electrical conductivity, abundant active sites and controllable morphology structure, thereby solving the problems of poor electrical conductivity and low stability of MOF materials in the prior art.

[0039] 2. The characterization test results of the hollow superstructure Co@C / N composite material in the present invention show that selective etching and high-temperature pyrolysis can effectively expose more metal active sites, which is beneficial to improving the electron transfer rate of the material.

[0040] 3. Since the material-modified electrode used in the present invention not only has good electrochemical performance and stability, but also has excellent responsiveness to the quantitative detection of hydrogen peroxide, the hydrogen peroxide electrochemical sensor prepared using the hollow superstructure Co@C / N composite material has the characteristics of high sensitivity, low detection limit, wide detection linear range, etc., and has good application prospects for the actual detection of hydrogen peroxide, and is expected to be widely used in the field of small molecule detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Schematic diagram of an X-ray diffraction diagram of a hollow superstructure Co@C / N composite material according to a specific embodiment of the present invention;

[0042] Figure 2a A schematic diagram of a scanning electron microscope image of a hollow superstructure Zn / Co ZIF material according to a specific embodiment of the present invention;

[0043] Figure 2b A schematic diagram of a scanning electron microscope image of a hollow superstructure Co@C / N composite material according to a specific embodiment of the present invention;

[0044] Figure 3a A schematic diagram showing a comparison of cyclic voltammetry curves of an electrochemical sensor constructed with a hollow superstructure Co@C / N composite material in response to different concentrations of hydrogen peroxide in accordance with a specific embodiment of the present invention;

[0045] Figure 3b A schematic diagram of a linear relationship between hydrogen peroxide concentration and peak current of an electrochemical sensor constructed with a hollow superstructure Co@C / N composite material according to a specific embodiment of the present invention;

[0046] Figure 4a A schematic diagram of the chronoamperometric response of an electrochemical sensor constructed of a hollow superstructure Co@C / N composite material to hydrogen peroxide according to a specific embodiment of the present invention;

[0047] Figure 4bThis is a schematic diagram of the linear relationship between the hydrogen peroxide concentration and the current of the electrochemical sensor constructed with the hollow superstructure Co@C / N composite material according to a specific embodiment of the present invention. DETAILED DESCRIPTION

[0048] The present invention is further explained below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.

[0049] The preparation method of the hollow superstructure Co@C / N composite material comprises the following steps:

[0050] Sa100. The ZIF material with a bimetallic center was prepared by coprecipitation method; after the reaction was completed, the first dispersion was washed and dispersed for later use.

[0051] Sa200. The first dispersion prepared in step Sa100 is selectively etched to obtain a hollow super-structure ZIF material.

[0052] Sa300. The hollow super structure ZIF material prepared in step Sa200 is subjected to high temperature pyrolysis to obtain a hollow super structure Co@C / N composite material.

[0053] It should be noted that step Sa100 includes the following specific steps:

[0054] Sa110. Weigh an artificially preset mass of divalent metal salts of zinc and cobalt and dissolve them.

[0055] Sa120. Weigh a preset mass of the organic ligand 2-methylimidazole and dissolve it in the solvent obtained in step Sa110, and then dissolve it by ultrasonication.

[0056] Sa130. The mixed solution obtained in step Sa120 is mixed and allowed to stand to produce a ZIF material with a bimetallic center; the standing time ranges from 2h to 12h.

[0057] Sa140. After the reaction in step Sa130 is completed, the first dispersion is obtained by washing and dispersing.

[0058] In this specific embodiment, the divalent metal salts of zinc and cobalt in step Sa110 include cobalt acetate and zinc acetate, and the molar ratio of zinc acetate to cobalt acetate is 20:1 to 100:1.

[0059] It should be further explained that the color of the first dispersion obtained in step Sa140 is purple.

[0060] It should be noted that step Sa200 includes the following specific steps:

[0061] Sa210. Add the first dispersion obtained in step Sa140 into an organic acid solution for etching; the etching time ranges from 2h to 12h.

[0062] Sa220. The solution obtained in step S210 is centrifuged, washed and dried to obtain a hollow super-structure ZIF material.

[0063] It should be noted that in step S210, the organic acid solution is added to the first dispersion, and after stirring, the solution becomes turbid and a purple solid is precipitated.

[0064] In this specific embodiment, the organic acid solution in step Sa210 is benzoic acid, salicylic acid, citric acid, or tannic acid; the concentration range of the organic acid solution is 0.01 mmol·L -1 ~0.1mmol·L -1 .

[0065] It should be noted that step Sa300 includes the following specific steps:

[0066] Sa310. Place the hollow superstructure ZIF material obtained in step Sa220 into a tubular furnace, and then calcine it in an inert gas atmosphere and maintain the manually preset calcination time; the calcination temperature range is 600°C to 1200°C, and the heating rate is 2°C / min to 10°C / min.

[0067] Sa320. The product of step Sa310 is naturally cooled to room temperature and then taken out and ground to obtain a hollow superstructure Co@C / N composite material.

[0068] It should be further explained that the hollow superstructure Co@C / N composite material is black powder.

[0069] A method for constructing a hydrogen peroxide electrochemical sensor using a hollow superstructure Co@C / N composite material comprises the following steps:

[0070] Sb100. The bare glassy carbon electrode was polished, and after passing the inspection, it was ultrasonically cleaned with ethanol and distilled water respectively, and then blown dry.

[0071] Sb200. After grinding the hollow superstructure Co@C / N composite material, it is taken out according to the manually preset mass and then put into the polymerizer solution for ultrasonic dispersion to obtain the second dispersion.

[0072] Sb300. Take a drop of the second dispersion and apply it to the bare glassy carbon electrode obtained after the treatment in step Sb100 and dry it naturally to obtain a bare glassy carbon electrode modified by a hollow superstructure Co@C / N composite material.

[0073] Sb400. A hydrogen peroxide electrochemical sensor was constructed using a saturated calomel electrode as the reference electrode, a platinum wire electrode as the counter electrode, and a bare glassy carbon electrode modified with a hollow superstructure Co@C / N composite material as the working electrode.

[0074] In this specific embodiment, the manually preset mass range in step Sb200 is 1 mg to 5 mg; the polymerizing agent is nafion and chitosan or isopropanol or DMF or ethanol; and the concentration of the polymerizing agent-ethanol is 1% to 5%.

[0075] It should be further explained that the electrochemical tests all adopt the three-electrode system in step Sb400.

[0076] A method for detecting hydrogen peroxide using a hydrogen peroxide electrochemical sensor comprises the following steps:

[0077] Sc100. The electrolyte is prepared using KOH solution.

[0078] The cyclic voltammetry curve of the sample was measured by cyclic voltammetry using an electrochemical workstation at room temperature.

[0079] Sc300. The chronoamperometric curve of the sample was tested using the chronoamperometric response method at room temperature.

[0080] It should be noted that the method for detecting hydrogen peroxide of the present invention is used to demonstrate that the constructed hydrogen peroxide electrochemical sensor has excellent responsiveness to hydrogen peroxide and has the characteristics of low detection limit, wide linear range, etc.

[0081] In this specific embodiment, the concentration range of the KOH solution prepared in Sc100 is 0.01 mol / L to 0.5 mol / L, which is used to prepare the hydrogen peroxide base solution.

[0082] The concentration range of the hydrogen peroxide base solution is 0.1 mmol / L to 20 mmol / L, and it is used as a hydrogen peroxide standard solution for electrochemical determination.

[0083] In this specific embodiment, the scan rate in the cyclic voltammetry in Sc200 is 20 mV / s to 200 mV / s, the potential range is -2 V to +1 V, and the number of cycles is 0 to 20.

[0084] The concentration of hydrogen peroxide added in the chronoamperometric response method in Sc300 is 0 mmol / to 1 mmol / L, and the time interval is 10 s / time to 100 s / time.

[0085] Example 1

[0086] Based on the specific methods of the above embodiments, the specific steps of Embodiment 1 are as follows:

[0087] Take 0.2857g Zn(CH3COO)2·2H2O and 0.0162g Co(CH3COO)2·4H2O and add them to 5mL water and stir until the solution is clear.

[0088] Configure 0.5mmol·L -1 CTAB solution: 1.1166 g of organic ligand 2-methylimidazole was dissolved in 5 mL of CTAB solution, and ultrasonicated until the ligand was completely dissolved. Then, the ligand solution was added to the above metal mixed solution, and the solution was allowed to stand for 2 hours after it became turbid.

[0089] After the reaction, the mixture was washed three times with deionized water by centrifugation, and finally dispersed in 10 mL of H2O for later use. The 10 mL of the first dispersion was placed in a 250 mL beaker, and 100 mL of 10 -4 mol·L -1 After stirring the benzoic acid aqueous solution for 6 hours, the solution became turbid and a purple solid precipitated, which was washed three times with deionized water and methanol respectively by centrifugation, and then dried at 80°C to obtain a hollow superstructure Zn / Co ZIF.

[0090] The prepared hollow superstructure ZIF material was placed in a graphite porcelain boat and then placed in a tubular furnace. It was heated to 900°C at a heating rate of 5°C / min in an argon atmosphere. After keeping it for 2 hours, it was naturally cooled to room temperature. The sample was taken out and ground to obtain a hollow superstructure Co@C / N composite material.

[0091] The obtained hollow superstructure Co@C / N composite material was ground in an agate mortar for 30 minutes, and then 3 mg of the sample was taken and put into 1 ml of 2% Nafion-ethanol solution. Ultrasonication was used for 30 minutes to evenly disperse the sample and the solvent to obtain a second dispersion of the above material.

[0092] The bare glassy carbon electrode (GCE) was pretreated by polishing with Al2O3 suspension. After passing the inspection, it was ultrasonically cleaned with ethanol and distilled water for 1 min respectively. After being blown dry with N2, 10 μL of the second dispersion droplet was applied to the GCE and dried naturally to obtain a hollow superstructure Co@C / N composite modified glassy carbon electrode for use.

[0093] The electrochemical tests all adopted a three-electrode system, with a saturated calomel electrode as the reference electrode, a platinum wire electrode as the counter electrode, and a bare glassy carbon electrode modified with the above-mentioned hollow superstructure Co@C / N composite material as the working electrode to construct an electrochemical system as a hydrogen peroxide sensor.

[0094] 0.1mol / L KOH solution was used as the electrolyte for the detection of hydrogen peroxide; cyclic voltammetry was used to detect the concentration response of hydrogen peroxide. The scan rate was 20mV / s, the potential range was -0.5V~+0.1V, and the number of cycles was 4. With the change of hydrogen peroxide concentration, the response of the CV curve changed significantly, and the peak current of the reduction peak increased with the increase of hydrogen peroxide concentration. The peak current was fitted with the hydrogen peroxide concentration, and it was found that the two had an excellent linear relationship, indicating that the electrochemical sensor constructed with the hollow superstructure Co@C / N composite material can be used to quantitatively detect the content of hydrogen peroxide in the solution.

[0095] At this working potential, the same volume of hydrogen peroxide solution with different concentrations was continuously added at the same time interval to perform chronoamperometric response measurement to determine the detection limit of hydrogen peroxide by the electrochemical sensor constructed with the hollow superstructure Co@C / N composite material. The concentration of hydrogen peroxide added in the chronoamperometric method was 0mmol / L~1mmol / L, and the time interval was 100s / time. Its response current increased with the increase of the concentration of hydrogen peroxide solution, and the current could be stabilized in a short time. When the concentration of hydrogen peroxide was 4×10 -5 mol·L -1 ~1×10 -2 mol·L -1 In the range of , after fitting, it was found that the response current value had an excellent linear relationship with the concentration of hydrogen peroxide solution, R 2 =0.9988.

[0096] Example 2

[0097] Based on the specific method of the above embodiment, the specific steps of Embodiment 2 are as follows:

[0098] Take 0.2857g Zn(CH3COO)2·2H2O and 0.0081g Co(CH3COO)2·4H2O and add them to 5mL water and stir until the solution is clear.

[0099] Configure 0.5mmol·L -1 CTAB solution: 1.1166 g of organic ligand 2-methylimidazole was dissolved in 5 mL of CTAB solution, and ultrasonicated until the ligand was completely dissolved. Then, the ligand solution was added to the above metal mixed solution, and the solution was allowed to stand for 2 hours after it became turbid.

[0100] After the reaction, the mixture was washed three times with deionized water by centrifugation, and finally dispersed in 10 mL of H2O for later use. The 10 mL of the first dispersion was placed in a 250 mL beaker, and 100 mL of 10 -3 mol·L -1After stirring the benzoic acid aqueous solution for 3 hours, the solution became turbid and a purple solid precipitated, which was washed three times by centrifugation with deionized water and methanol, and then dried at 80°C to obtain a hollow superstructure Zn / Co ZIF material.

[0101] The prepared hollow superstructure ZIF material was placed in a graphite porcelain boat and then placed in a tubular furnace. It was heated to 1200°C at a heating rate of 10°C / min in an argon atmosphere. After keeping it for 1 hour, it was naturally cooled to room temperature. The sample was taken out and ground to obtain a hollow superstructure Co@C / N composite material.

[0102] The obtained hollow superstructure Co@C / N composite material was ground in an agate mortar for 30 minutes, and then 3 mg of the sample was taken and put into 1 mL of 1% chitosan-acetic acid solution. Ultrasonication was used for 30 minutes to evenly disperse the sample and the solvent to obtain a second dispersion of the above material.

[0103] The bare glassy carbon electrode (GCE) was pretreated by polishing with Al2O3 suspension. After passing the inspection, it was ultrasonically cleaned with ethanol and distilled water for 1 min respectively. After being blown dry with N2, 10 μL of the second dispersion droplet was applied to the GCE and dried naturally to obtain a hollow superstructure Co@C / N composite modified glassy carbon electrode for use.

[0104] The electrochemical tests all adopted a three-electrode system, with a saturated calomel electrode as the reference electrode, a platinum wire electrode as the counter electrode, and a bare glassy carbon electrode modified with the above-mentioned hollow superstructure Co@C / N composite material as the working electrode to construct an electrochemical system as a hydrogen peroxide sensor.

[0105] 0.1mol / LKOH solution was used as the electrolyte for the detection of hydrogen peroxide; cyclic voltammetry was used to detect the concentration response of hydrogen peroxide. The scan rate was 100mV / s, the potential range was -0.8V~+0.4V, and the number of cycles was 6. With the change of hydrogen peroxide concentration, the response of the CV curve changed significantly, and the peak current of the reduction peak increased with the increase of hydrogen peroxide concentration. The peak current was fitted with the hydrogen peroxide concentration, and it was found that the two had an excellent linear relationship, indicating that the electrochemical sensor constructed with the hollow superstructure Co@C / N composite material can be used to quantitatively detect the content of hydrogen peroxide in the solution.

[0106] At this working potential, the same volume of hydrogen peroxide solution with different concentrations was continuously added at the same time interval to perform chronoamperometric response measurement to determine the detection limit of hydrogen peroxide by the electrochemical sensor constructed with the hollow superstructure Co@C / N composite material. The concentration of hydrogen peroxide added in the chronoamperometric method was 0mmol / L~1mmol / L, and the time interval was 100s / time. Its response current increased with the increase of the concentration of hydrogen peroxide solution, and the current could be stabilized in a short time. When the concentration of hydrogen peroxide was 5×10 -5 mol·L -1 ~1.8×10 -2 mol·L -1 In the range of , after fitting, it was found that the response current value had an excellent linear relationship with the concentration of hydrogen peroxide solution, R 2 =0.9974.

[0107] Example 3

[0108] Based on the specific method of the above embodiment, the specific steps of Embodiment 3 are as follows:

[0109] Take 0.2700g Zn(CH3COO)2·2H2O and 0.0398g Co(CH3COO)2·4H2O and add them to 5ml water, and stir until the solution is clear.

[0110] Configure 0.5mmol·L -1 CTAB solution: 1.1166 g of organic ligand 2-methylimidazole was dissolved in 5 ml of CTAB solution, and ultrasonicated until the ligand was completely dissolved. Then, the ligand solution was added to the above metal mixed solution, and the solution was allowed to stand for 2 hours after it became turbid.

[0111] After the reaction, the mixture was washed three times with deionized water by centrifugation, and finally dispersed in 10 mL of H2O for later use. The 10 mL first dispersion was placed in a 250 mL beaker, and 100 mL of 10 -4 mol·L -1 After stirring the benzoic acid aqueous solution for 2 hours, the solution became turbid and a purple solid precipitated, which was washed three times by centrifugation with deionized water and methanol, and then dried at 80°C to obtain a hollow superstructure Zn / Co ZIF material.

[0112] The prepared hollow superstructure ZIF material was placed in a graphite porcelain boat and then placed in a tubular furnace. It was heated to 1000°C at a heating rate of 2°C / min in an argon atmosphere. After keeping it for 3 hours, it was naturally cooled to room temperature. The sample was taken out and ground to obtain a hollow superstructure Co@C / N composite material.

[0113] The obtained hollow superstructure Co@C / N composite material was ground in an agate mortar for 30 minutes, and then 3 mg of the sample was taken and put into 1 mL of 5% nafion-ethanol solution. Ultrasonication was used for 30 minutes to evenly disperse the sample and the solvent to obtain a second dispersion of the above material.

[0114] The bare glassy carbon electrode (GCE) was pretreated by polishing with Al2O3 suspension. After passing the inspection, it was ultrasonically cleaned with ethanol and distilled water for 1 min respectively. After being blown dry with N2, 10 μL of the second dispersion droplet was applied to the GCE and dried naturally to obtain a hollow superstructure Co@C / N composite modified glassy carbon electrode for use.

[0115] The electrochemical tests all adopted a three-electrode system, with a saturated calomel electrode as the reference electrode, a platinum wire electrode as the counter electrode, and a bare glassy carbon electrode modified with the above-mentioned hollow superstructure Co@C / N composite material as the working electrode to construct an electrochemical system as a hydrogen peroxide sensor.

[0116] 0.1mol / LKOH solution was used as the electrolyte for the detection of hydrogen peroxide; cyclic voltammetry was used to detect the concentration response of hydrogen peroxide. The scan rate was 50mV / s, the potential range was -0.4V~0V, and the number of cycles was 8. With the change of hydrogen peroxide concentration, the response of the CV curve changed significantly, and the peak current of the reduction peak increased with the increase of hydrogen peroxide concentration. The peak current was fitted with the hydrogen peroxide concentration, and it was found that the two had an excellent linear relationship, indicating that the electrochemical sensor constructed with the hollow superstructure Co@C / N composite material can be used to quantitatively detect the content of hydrogen peroxide in the solution.

[0117] At this working potential, the same volume of hydrogen peroxide solution with different concentrations was continuously added at the same time interval to perform chronoamperometric response measurement to determine the detection limit of hydrogen peroxide by the electrochemical sensor constructed with the hollow superstructure Co@C / N composite material. The concentration of hydrogen peroxide added in the chronoamperometric method was 0mmol / L~1mmol / L, and the time interval was 50s / time. Its response current increased with the increase of the concentration of hydrogen peroxide solution, and the current could be stabilized in a short time. When the concentration of hydrogen peroxide was 2×10 -5 mol·L -1 ~3×10 -2 mol·L -1 In the range of , after fitting, it was found that the response current value had an excellent linear relationship with the concentration of hydrogen peroxide solution, R 2 =0.9957.

[0118] In the above detailed description, various features are grouped together in a single embodiment to simplify the disclosure. This method of disclosure should not be interpreted as reflecting an intention that the embodiments of the claimed subject matter require more features than are clearly stated in each claim. On the contrary, as reflected in the appended claims, the invention is in a state of having less than all the features of the disclosed individual embodiments. Therefore, the appended claims are hereby expressly incorporated into the detailed description, with each claim standing on its own as a separate preferred embodiment of the invention.

[0119] The disclosed embodiments are described above to enable any person skilled in the art to implement or use the present invention. Various modifications of these embodiments are obvious to those skilled in the art, and the general principles defined herein may also be applied to other embodiments without departing from the spirit and scope of the present disclosure. Therefore, the present disclosure is not limited to the embodiments given herein, but is consistent with the broadest scope of the principles and novel features disclosed in this application.

[0120] The above description includes examples of one or more embodiments. Of course, it is not possible to describe all possible combinations of components or methods for the purpose of describing the above embodiments, but it should be recognized by those skilled in the art that the various embodiments may be further combined and arranged. Therefore, the embodiments described herein are intended to cover all such changes, modifications and variations that fall within the scope of protection of the appended claims. In addition, with respect to the term "comprising" used in the specification or claims, the word is covered in a manner similar to the term "including", just as "including," is explained as a transitional word in the claims. In addition, any term "or" used in the specification of the claims is intended to mean "non-exclusive or".

[0121] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a hollow superstructure Co@C / N composite material, characterized in that: The following steps are involved: Sa100. Preparation of ZIF materials with bimetallic centers by coprecipitation; washing and dispersing the first dispersion prepared after the reaction; Sa200. The first dispersion prepared in step Sa100 is selectively etched to obtain a hollow super-structure ZIF material; Sa300. The hollow super structure ZIF material prepared in step Sa200 is subjected to high temperature pyrolysis to obtain a hollow super structure Co@C / N composite material.

2. The method for preparing the hollow superstructure Co@C / N composite material according to claim 1, characterized in that: The step Sa100 comprises the following specific steps: Sa110. Weigh and dissolve the manually preset mass of zinc and cobalt divalent metal salts; Sa120. Weigh the manually preset mass of the organic ligand 2-methylimidazole and dissolve it in the solvent obtained in step Sa110, and then dissolve it by ultrasound; Sa130. The mixed solution obtained in step Sa120 is mixed and allowed to stand to produce the ZIF material of the bimetallic center; the standing time ranges from 2h to 12h; Sa140. After the reaction in step Sa130 is completed, the first dispersion is obtained by washing and dispersing.

3. The method for preparing the hollow superstructure Co@C / N composite material according to claim 2, characterized in that: The step Sa200 comprises the following specific steps: Sa210. The first dispersion obtained in step Sa140 is added to an organic acid solution for etching; the etching time ranges from 2h to 12h; Sa220. The solution obtained in step S210 is centrifuged, washed and dried to obtain a hollow super-structure ZIF material.

4. The method for preparing the hollow superstructure Co@C / N composite material according to claim 3, characterized in that: The step Sa300 comprises the following specific steps: Sa310. The hollow super structure ZIF material obtained in step Sa220 is placed in a tubular furnace, and then calcined in an inert gas atmosphere and maintained for a manually preset calcination time; the calcination temperature range is 600°C to 1200°C, and the heating rate is 2°C / min to 10°C / min; Sa320. The product of step Sa310 is naturally cooled to room temperature and then taken out and ground to obtain the hollow superstructure Co@C / N composite material.

5. The method for preparing the hollow superstructure Co@C / N composite material according to claim 4, characterized in that: The divalent metal salt of zinc and cobalt in step Sa110 comprises cobalt acetate and zinc acetate, and the molar ratio of zinc acetate to cobalt acetate is 20:1 to 100:1; The organic acid solution in step Sa210 is benzoic acid, salicylic acid, citric acid or tannic acid; the concentration range of the organic acid solution is 0.01 mmol·L -1 ~0.1mmol·L -1 .

6. A method for constructing a hydrogen peroxide electrochemical sensor using the hollow superstructure Co@C / N composite material according to claim 5, characterized in that: The following steps are involved: Sb100. The bare glassy carbon electrode was polished, and after passing the inspection, it was ultrasonically cleaned with ethanol and distilled water respectively, and then dried; Sb200. After the hollow super structure Co @ C / N composite material is ground, it is taken out according to the preset mass and then ultrasonically dispersed in a polymerizing agent solution to obtain a second dispersion; Sb300. Take the second dispersion droplets and apply them to the bare glassy carbon electrode obtained after the treatment in step Sb100 and dry them naturally to obtain a bare glassy carbon electrode modified with a hollow superstructure Co@C / N composite material; Sb400. The hydrogen peroxide electrochemical sensor is constructed by using a saturated calomel electrode as a reference electrode, a platinum wire electrode as a counter electrode, and a bare glassy carbon electrode modified with the hollow superstructure Co@C / N composite material as a working electrode.

7. The method for constructing a hydrogen peroxide electrochemical sensor according to claim 6, characterized in that: The manually preset mass in step Sb200 is within a range of 1 mg to 5 mg; the polymerizing agent is nafion and chitosan or isopropanol or DMF or ethanol; and the polymerizing agent-ethanol concentration is 1% to 5%.

8. A method for detecting hydrogen peroxide using the hydrogen peroxide electrochemical sensor according to claim 7, characterized in that: The following steps are involved: Sc100. The electrolyte is prepared using KOH solution; Sc200. Cyclic voltammetry curves of samples were measured using cyclic voltammetry using an electrochemical workstation at room temperature; Sc300. The chronoamperometric curve of the sample was tested using the chronoamperometric response method at room temperature.

9. The method for detecting hydrogen peroxide according to claim 8, characterized in that: The concentration range of KOH solution prepared in Sc100 is 0.01mol / L to 0.5mol / L, which is used to prepare hydrogen peroxide base solution; The concentration range of the hydrogen peroxide base solution is 0.1 mmol / L to 20 mmol / L, and the base solution is used as a hydrogen peroxide standard solution for electrochemical determination.

10. The method for detecting hydrogen peroxide according to claim 9, characterized in that: In the cyclic voltammetry described in Sc200, the scan rate is 20 mV / s to 200 mV / s, the potential range is -2 V to +1 V, and the number of cycles is 0 to 20; The concentration of hydrogen peroxide added in the chronoamperometric response method described in Sc300 is 0 mmol / to 1 mmol / L, and the time interval is 10 s / time to 100 s / time.